The Illusory Death Penalty: Why America's Death Penalty Process Fails to Support the Economic Theories of Criminal Sanctions and Deterrence - Johnson, Allan D. (2001)
The central tenet of the economic approach to criminal law is deterrence. This approach provides a useful tool to analyze the theoretical justifications of capital punishment. From an economic view, the death penalty is a logical extension of the criminal justice system's primary goal of deterrence and is arguably necessary to solve inherent deterrence problems such as marginal deterrence and discounting. Nevertheless, current empirical research on capital punishment in America has shown that, in practice, capital punishment provides, at best, very little deterrence to serious crimes. This Note discusses a few of the possible reasons why America's death penalty process yields so little deterrence to crime in comparison to its theoretical level of deterrence. The Note argues that the great delay between conviction and actual execution defeats any theoretical deterrent effect of capital punishment. The Note concludes by suggesting a few ways in which America could reform its death penalty process to serve as a greater deterrent, including the possibility that the most efficient solution may be to abolish the death penalty